1979
DOI: 10.1161/01.str.10.3.292
|View full text |Cite
|
Sign up to set email alerts
|

EEG monitoring for induced hypotension for surgery of intracranial aneurysms.

Abstract: SUMMARY EEG was monitored at bilateral scalp sites outside the operative field during hypotensive aneurysm surgery in 21 patients. Mean arterial blood pressure at axillary level was 50-60 mm Hg (average 55 mm) for 1.9-5.3 hours (average 3.6). Four new deficits were noted immediately post-operatively, all related to the operated site: these were attributable to intra-operative rupture with forced vascular clipping, vasospasm, or edema. In no instance was hypotension solely responsible for a new deficit. EEG sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…None of them was considered to have a low risk of bias. The best current evidence showed that the heart rate may be increased or may remain stable during deliberate hypotension, depending on the drug used to induce hypotension 55,56, 66,69,79,91,154 . Similarly, the cardiac output may or may not change depending on the anaesthetic technique used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of them was considered to have a low risk of bias. The best current evidence showed that the heart rate may be increased or may remain stable during deliberate hypotension, depending on the drug used to induce hypotension 55,56, 66,69,79,91,154 . Similarly, the cardiac output may or may not change depending on the anaesthetic technique used.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral damage or neurological deficit 79,127 , stroke 90 , dysrhythmia 123 , cardiac arrest 111 or even death 111,127 following hypotensive anaesthesia have been reported. Most of these cases involved patients with pre-existing disease.…”
Section: Discussionmentioning
confidence: 99%
“…Six of these eight patients awoke with new neurological deficits. In an earlier report, Jones,et al,6 using conventional eight-channel EEG monitoring during aneurysm surgery, were unable to demonstrate a similar association between persistent EEG abnormalities and new postoperative neurological deficits. In their investigations, the EEG monitor failed to identify intraoperative ischemia in three of the four patients with postoperative focal deficits.…”
Section: Discussionmentioning
confidence: 89%
“…'8 '25 Electroencephalographic (EEG) monitoring with conventional eight-to 16-channel apparatus is a reliable means of evaluating cerebral perfusion during carotid endarterectomy (CEA), 21' 24' 26 cardiopulmonary bypass procedures, 22 and controlled hypotension.~'6 Intraoperative EEG monitoring during aneurysm surgery has received little attention, however, primarily due to problems with electrode placement, particularly over the operative region. 6 Recent advances in electronic technology have simplified the use ofintraoperative EEG monitoring. Commercially available computerized monitors that process the EEG signal into a concise form utilizing fast-Fourier analysis have been developed to simplify the recognition and interpretation of EEG changes during anesthesia.…”
mentioning
confidence: 99%
“…EEG and ECoG allow direct monitoring of cortical activity and indirect assessment of adequate cortical perfusion (119,130) in various intraoperative settings, such as during induced hypotension and temporary vessel occlusion (35,43,57,61,130). Cortical monitoring can be performed by scalp or direct cortical registration (which requires a wide cortical exposure) and can be performed as a passive registration of the cortical spontaneous electrical activity (EEG) or as the evaluation of transcortical stimulus transmission after active stimulation (delayed cortical response [DCR]).…”
Section: Neurophysiologic Monitoringmentioning
confidence: 99%